Raddeanin A promotes the apoptosis of gastric cancer in conjunction with autophagy inhibitor Hydroxychloroquine via MAPK signaling pathway - Yuhao Teng; Ying Xing; Weiwei Xue; Yue Hu; Zirui Li; Jun Qian; Ruiping Wang (Journal of Traditional and Complementary Medicine)
Purpose: Gastric cancer (GC) is among the malignant cancers with the highest incidence and mortality worldwide. As GC is not very sensitive to current chemotherapy drugs, there is an urgent need to develop new effective drugs. Raddeanin A (RA) is extracted from the traditional Chinese medicine Anemone raddeana Regel, which has an anti-cancer effect. The purpose of this study was to explore the effects of RA on GC in vitro and in vivo. Methods: We explored the targets of RA in GC through network pharmacology. MTT assay, flow cytometry, Western blotting, and other methods were used to detect the effects of RA on the proliferation, apoptosis, and autophagy of GC cells. After preconditioning with hydroxychloroquine (HCQ) and rapamycin, we observed the effects of RA-induced autophagy on apoptosis. We further verified the antitumor effect and safety of RA in vivo. Using SNU-1 xenograft tumor model in nude mice, tumor volume was observed and liver toxicity was observed by immunohistochemistry. Results: Many cancer-related signaling pathways were visualized using Cytoscape software. Among them, the MAPK signaling pathway was one of the highest-ranked pathways. The MTT assay results suggested that RA could inhibit the proliferation of HGC-27 and SNU-1 cells effectively. Flow cytometry and Western blotting confirmed that RA could significantly induce apoptosis of HGC-27 and SNU-1 cells. Electron microscopy and Western blotting demonstrated that RA could induce autophagy of HGC-27 and SNU-1 cells. Further experiments suggested that HCQ, an autophagy inhibitor, could enhance the capacity of RA to induce apoptosis. In animal studies, we found that intraperitoneal injection of RA could effectively and safely inhibit gastric tumors. Conclusions: RA significantly inhibited the proliferation and induced autophagy and apoptosis of GC cells. In combination with HCQ, RA-induced apoptosis increased in vitro. The combined application of RA and autophagy inhibitors may serve as an added approach to the treatment of GC, but the underlying mechanism needs further exploration. In vivo, it was observed that RA has a good antitumor effect without increasing liver toxicity.